Physiological pattern changes in response to a simulated competition in elite women's artistic gymnasts - Isacco, L.; Ennequin, G.; Cassirame, J.; Tordi, N. (The Journal of Strength and Conditioning Research, 2019)
The outstanding progress in women's artistic gymnastics in recent decades has led to increased technical and physiological demands. The aim of this study was to investigate (a) the physiological demands of elite French gymnasts and (b) the impact of a competitive routine on physiological pattern changes. Fourteen French elite female gymnasts performed anthropometric measurements, physical fitness tests, and a simulated 4-event competition. Heart rate (HR) was continuously recorded throughout the duration of the simulated competition. Blood lactate concentrations were assessed at rest, before the beginning and at 2, 4, and 10 minutes after completion of the routine on each apparatus. Isometric handgrip strength and anaerobic endurance and power were assessed during the simulated competition. The highest values of HR and blood lactate concentrations were reached during the floor and uneven bar exercises. Blood lactate concentrations and HR kinetics were apparatus dependent and values remained significantly increased at 10 minutes of recovery compared with resting data. Anaerobic endurance and power decreased significantly as the competition progressed (p < 0.001). The present results show specifically cardiorespiratory and anaerobic apparatus-dependent responses throughout a simulated competition. Recovery approaches seem relevant to prevent and minimize fatigue and optimize performance in these athletes.The purpose of this study was to determine whether a battery of anthropometric and lower and upper body strength and speed and power tests predicted selection of young volleyball players for a Junior National Team by expert coaches. Fifty-two male junior volleyball players (14.8 ± 0.5 years, height: 1.84 ± 0.05 m, body mass: 72.5 ± 7.1 kg) took part in a training camp and underwent a selection procedure by expert coaches' of the junior national team. Anthropometric data and fitness tests results were obtained and players were graded on a scale from 0 to 100 on the basis of their performance in a volleyball tournament. Selected players were superior in the majority of measured variables (p < 0.017) and had higher grading scores compared with nonselected players (85.3 ± 4.1 vs. 70.5 ± 5.6, respectively, p < 0.01). The combination of spike jump and reach (SJR) test and 3-kg medicine ball throw (MB3) velocity explained 63.5% of the variance in expert coaches' grading (p < 0.001). A multivariate discriminant analysis yielded a significant discriminant function (Wilk's lambda = 0.55, ?2 = 29.324, p < 0.001, ?2 = 0.82). Spike jump and reach and MB3 were the only variables that contributed to the discriminant function (standardized function coefficients: SJR = 0.68, MB3 = 0.67). Cross-validation results showed that selection was correctly predicted in 14 of the 16 selected players (predictive accuracy: 87.5%) and in 32 of the 36 nonselected players (predictive accuracy: 88.9%). The SJR and MB3 fitness tests can predict a large portion of the variance of expert coaches' grading and successfully discriminate elite young male volleyball players for selection vs. nonselection for a junior national team. This result is very important as performance testing during a selection process may be reduced to only 2 measurements.